Answer:
k = 9
Step-by-step explanation:
n = 3, so substitute 3 for n in the equation
k = 3(3)
k = 9
Answer:
positive is the correct answer
Answer:
3.7
Step-by-step explanation:
2r(pi)(∅/360)
2*3*(pi)*(70/360)
6*(pi)*(0.19444...)
3.665191429188092
3.7
Answer:
30
Step-by-step explanation:
Original Equation: 2(7 + 8)
So you have to multiply 2 by 7 which equals 14
Then you multiply 2 by 8 which equals 16
Your equation should now look like this: 14 + 16
Add 14 and 16 together.
Your answer is 30
Hope I helped :)
Please condsider brainliest